Population fluctuation of Culicoides insignis Lutz (Diptera: Ceratopogonidae) in Posadas, Misiones, Argentina - Ayala, Mahia Mariel (2018)
The Bluetongue virus appears to be restricted in Argentina to the northeasternarea of the country. In the Neotropical region the main vector could be Culicoides insignis Lutz. This study was aimed to determine the population fluctuation of C. insignis in Posadas city and test the influence of climatic variables as determinants of the abundance of this species. The specimens were collected in Posadas city using CDC light traps from January to December 2013. The abundance of C. insignis in relation to environmental variables was analyzed using multivariate linear regression. A total of 2,952 specimens of C. insigniswere collected representing 93.4% of the total Culicoides captured. The multivariate linear regression analyses show that the monthly mean relative humidity was the variable that best explained the population dynamics of C. insignis in the work area. The pathogen transmission is probably influenced by the abundance of the vector in this area. The population peaks observed are indicative of periods when there should be more control to prevent transmissionof the disease. This is the first report of population fluctuation of C. insignis in northeastern Argentina.